Typology assessment of dairy cattle production in the major productive region of Tunisia. - hamzaoui, SARRA (Indian Journal of Dairy Science, 2026)
The study aimed to identify dairy systems related to purebred cattle in Tunisia and their effects on milk production and quality. A survey of 102 breeders across 17 governorates focused on feeding practices and milk parameters. Principal Component Analysis (PCA) revealed three farm groups: Group I (51% of farms) relies on rainfed systems with limited forage; Group II (26%) employs mixed irrigation with moderate forage; and Group III (23%) uses irrigation, featuring larger farms and diverse diets. Significant differences were observed among groups in terms of farm size, cow numbers, and diet composition (P<0.0001). Results showed that Group III produced the highest daily milk yield (21.59 kg), while Group I had the lowest (16.45 kg). Fat content exceeded the national average in all groups, with Group III showing the highest at 38.2 g/L. Protein levels also surpassed average values, particularly in Group III (30 g/L). Group II had the highest urea content (44.81 mg/dL), indicating dietary imbalances. Overall, the analysis distinguished dairy farms by agricultural systems, with irrigated farms demonstrating superior milk production and quality for purebred cattle.